Surveillance, Race, Culture
XIII, 294 p. 1 illus.
Keywords: This collection of essays engages with a wide range of disciplines including art, performance, film and literature, to examine the myriad effects of contemporary surveillance on our cultural psyche. The volume expertly articulates the manner in which cultural productions have been complicit in watching, seeing and purporting to ‘know’ race. In our increasingly mediated world, our sense of community is becoming progressively virtual, and surveillant technologies impact upon subjectivity, resulting in multiple forms of artistic and cultural expression. As such, art, film, and literature provide a lens for the reflection of sociocultural concerns. In Surveillance, Race, Culture Flynn and Mackay skilfully draw together a diverse range of contributions to investigate the fundamental question of exactly how surveillant technologies have informed our notions of race, identity and belonging. .